The Creativity and Strategies of the Principal in Building School Branding at SDN Sengon I Purwosari - Mahmudah, Mahmudah; Thohirin, Ahmad; Wahyudi, M. Furqon (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
In the context of accelerating educational transformation and increasing demands for 21st-century competencies, school leadership plays a decisive role in shaping adaptive and sustainable learning environments. This study examines how transformational leadership of a school principal enhances teachers’ work motivation and pedagogical competence to improve instructional quality at the elementary level. A qualitative case study was conducted at SDN Gunting I Sukorejo using in-depth interviews, observations, and document analysis. Data were analyzed through data reduction, display, and verification, supported by methodological triangulation to ensure credibility. The findings indicate that visionary direction, continuous academic supervision, collaborative culture building, and teacher empowerment significantly strengthen intrinsic motivation and reflective pedagogical practices. These leadership strategies foster structured lesson planning, innovative instructional approaches, and greater student engagement. Moreover, the principal’s role extends beyond administrative coordination toward cultivating a professional learning ecosystem that supports adaptive and student-centered education. The novelty of this study lies in its integrated analysis of transformational leadership as a catalytic mechanism linking motivation reinforcement and pedagogical competence within a future-oriented elementary education framework. The study highlights the strategic repositioning of school principals as change agents who drive sustainable professional growth and educational innovation.